Changes to the gut microbiota induced by losartan contributes to its antihypertensive effects. (3rd February 2020) - Robles‐Vera, Iñaki; Toral, Marta; de la Visitación, Néstor; Sánchez, Manuel; Gómez‐Guzmán, Manuel; Muñoz, Raquel; Algieri, Francesca; Vezza, Teresa; Jiménez, Rosario; Gálvez, Julio; Romero, Miguel; Redondo, Juan Miguel; et al.
Abstract : Background and Purpose: Hypertension is associated with gut dysbiosis. Here we have evaluated the effects of the angiotensin receptor antagonist losartan on gut microbiota in spontaneously hypertensive rats (SHR) to assess their contribution to its antihypertensive effects. Experimental Approach: Twenty‐week‐old Wistar Kyoto rats (WKY) and SHR were treated with losartan for 5 weeks (SHR‐losartan). Faecal microbiota transplantation (FMT) was performed from donor SHR‐losartan group to recipient untreated‐SHR. Blood pressure (BP) was measured using tail‐cuff plethysmography. Composition of the gut microbiota was assessed by amplification of the V3‐V4 region of 16S rRNA gene. T cells were analysed in gut/aorta by flow cytometry. Key Results: Faeces from SHR showed gut dysbiosis, characterised by higher Firmicutes/Bacteroidetes ratios, lower acetate‐ and higher lactate‐producing bacteria, and lower levels of strict anaerobic bacteria, effects which were restored to normal by losartan. Improvement of gut dysbiosis was linked to higher colonic integrity and lower sympathetic drive in the gut. In contrast, hydralazine reduced BP, but it neither restored gut dysbiosis nor colonic integrity. FMT from SHR‐losartan to SHR reduced BP, improved the aortic endothelium‐dependent relaxation to ACh, and reduced NADPH oxidase activity. These vascular changes were accompanied by both increased Treg and decreased Th17 cell populations in the vascular wall. Conclusion and Implications: In SHR, losartan treatment reduced gut dysbiosis and sympathetic drive in the gut, thus improving gut integrity. The changes induced by losartan in gut microbiota contributed, in part, to protecting the vasculature and reducing BP, possibly by modulating the immune system in the gut.